The Continuous Evaluation and Improvement of Exit Exams in Higher Education: A Systematic Review - Teshome, Samson Worku (Lembaga Yasin AlSys, 2025)
Exit exams in higher education have become a significant tool for assessing the competencies of students and ensuring quality assurance. This systematic literature review examines the continuous evaluation and improvement of exit exams, focusing on their role in enhancing educational outcomes and employability opportunities. Utilizing the PRISMA framework and PICO methodology, this review synthesizes findings from 29 studies spanning various disciplines and geographical regions. The results reveal diverse approaches to improving exit exams, emphasizing feedback mechanisms, curriculum alignment, and technological advancements. A narrative analysis highlights the complexities and benefits of implementing such evaluations. This review concludes that while exit exams can enhance accountability and quality, they require careful design and continuous refinement to address challenges like equity and validity.